Meningkatkan Kesadaran akan Bahaya Cybercrime di Kalangan Siswa dan Siswi SMAN 12 Kota Tangerang Selatan - Ria Anhar; Shantika Dwi Kurniawati; Tiyas Cahyaning Wulan; Rivalno Putra; Dzulfikar Ali (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
The rapid advancement of information technology has significantly influenced the lifestyle of younger generations, especially students who are active users of digital platforms. Despite the convenience of accessing information and communication, there lies a hidden threat in the form of cybercrime. A lack of awareness and understanding among students regarding the types and risksof cybercrime makes them vulnerable as both victims and perpetrators. This community service program aimed to enhance students’ digital literacy and awareness of cyber threats at SMAN 12 Kota Tangerang Selatan through educational activities. The program was conducted using lectures, interactive discussions, and case studies relevant to students' daily digital experiences. The results showed a notable increase in participants' understanding of digital safety issues and a stronger commitment to responsible and ethical use of technology. This initiative is expected to serve as an initial step in fostering a safe and healthy digital culture within the school environment